A geographical study of crime against women in India - Shreyanshi Shukla; Seema Tiwari (National Geographical Journal of India, 2021)
Despite the existence of various laws and legislations, the crime against women has been increasing continuously. The crime rate (per lakh women) in India has drastically increased from 18 to 58.8 from 2010 to 2018. This paper aims to reveal the trend and spatial pattern of the level of vulnerability of women’s in India and also analyse the correlation between some socio-economic indicators and crime rates against women. The standard deviation (SD) technique is used to measure the respective vulnerability of women in different states/UTs of India concerning the national average. Pearson coefficient of correlation is used to find out the correlation between the rate of crime and socio-economic indicators. The average crime rate against women from 2010 to 2018 is taken as a standard variable. Due to the under-reporting of such kinds of incidences, it is hard to find the exact trend and spatial pattern. If the official data are likely to show the reality then it is possible to look at regional patterns and it can lead to meaningful hypotheses formation for future work.